I am trying to solve: Let, $$\vec a, \vec b ∈ \mathbb{R}^2 $$ $$\vec a = (a_1, a_2), \vec b = (b_1, b_2)$$ $$\vec c = \vec a + \vec b $$ Find vectors a, b, so that: $$ \vert \vec c \vert = \vert \vec a \vert + \vert \vec b \vert $$ $$ \sqrt {(a_1 + b_1)^2 + (a_2+b_2)^2} = \sqrt {a_1^2+a_2^2} + \sqrt {b_1^2+b_2^2} \text{ (1)}$$ Solving it, I get $$ (a_2*b_1 - a_1*b_2)^2 = 0$$ $$ a_2*b_1 = a_1*b_2 $$

$$\text{When I pick } a = [7, 1], b=[-1, x],$$ $$ \text{I get } a = [7, 1], b = [-1, -\frac{1}{7}]$$ Substituting these values back in (1) does not give an equality. I can see that b is a vector in the opposite direction of a, so it sort of makes sense intuitively why the sum of a and b doesn't have the same magnitude as |a| + |b|. However, since solving the equation gives me the value for b2, I am confused about the result and why aren't both sides of (1) equal. Could someone please offer an explanation?



For the vectors:

$$|a+b| \leq |a|+|b|$$

When happen equality?

See this: Proof for triangle inequality for vectors

The equality happens when $a=k\cdot b$ with $k>0$.

Ps.: You are missing some evaluations. You are saying that the vectors $a$ and $b$ are in opposite directions what is not true (see above: $k>0$).

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.